2021
DOI: 10.1007/s00192-021-04696-z
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and anal incontinence among female gymnasts and cheerleaders—bother and associated factors. A cross-sectional study

Abstract: Introduction and hypothesis Artistic gymnastics, team gymnastics and cheerleading are sports including high-impact activities. It is presumed that the athletes’ pelvic floor must be functioning well to prevent urinary (UI) and anal incontinence (AI) during sports. The aim of this study was to investigate the prevalence and risk factors for UI and AI in female artistic gymnasts, team gymnasts and cheerleaders; the influence of UI and AI on daily living and sport performance; and the athletes’ know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Fifteen studies involved nulliparous participants [23, 24, 26, 27, 29, 31, 35, 37-39, 41, 42, 44, 45, 53] and 15 studies included both nulliparous and parous participants [8, 25, 28, 30, 32-34, 36, 40, 43, 46, 48, 50-52]. Two studies did not report information on parity of participants [47,49].…”
Section: Descriptive Analyses Of the Studies Excluding Information Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies involved nulliparous participants [23, 24, 26, 27, 29, 31, 35, 37-39, 41, 42, 44, 45, 53] and 15 studies included both nulliparous and parous participants [8, 25, 28, 30, 32-34, 36, 40, 43, 46, 48, 50-52]. Two studies did not report information on parity of participants [47,49].…”
Section: Descriptive Analyses Of the Studies Excluding Information Re...mentioning
confidence: 99%
“…Mixed urinary incontinence (MUI) was reported as the most prevalent form of UI in one study by Cardoso et al [27]. Anorectal dysfunction (ARD) was reported in nine studies with the prevalence of constipation/straining to defecate reported in all of these studies [8,26,28,29,31,32,34,46,47] and anal incontinence (AI) reported in four studies [26,29,46,47]. The prevalence of sexual dysfunction (SD) was reported in two studies [26,29], the prevalence of POP was reported in four studies [26,29,41,46] and the prevalence of pelvic pain was reported in two studies [24,45].…”
Section: Descriptive Analyses Of the Studies Excluding Information Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions could be under-recognized for several reasons. Studies showed that the athletes' knowledge of the pelvic floor muscles was low 8,11 , few had discussed their condition with coaches or medical personnel 7,8 , and only a minority of professionals were aware and consistently screened for PFD 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other PFD such as pelvic organ prolapse (POP) and anal incontinence (AI) evidence are still scant 4 . These disorders could interfere not only with the athletes 'personal and social lives, but also could affect their performance [6][7][8] . Nevertheless, several authors have already discussed that it is reasonable to assume that the overall problem could be underestimated 4,9 .…”
Section: Introductionmentioning
confidence: 99%